Solid pseudopapillary tumor of the pancreas: A case series of 9 patients - Selvinaz ÖZKARA; Fügen VARDAR AKER; Ali YİTİK and İlkay TOSUN and Abdullah SAĞLAM and Züleyha AKKAN ÇETİNKAYA and; stan GÜMRÜKÇÜ and; me TİSGAOĞLU (Turkish Journal of Gastroenterology, 2019)
-